Application of butterworth filter in face recognition system for grayscale static data [electronic resource] - 191440 Nurzal Effiyana Ghazali; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Telekomunikasi)) - Universiti Teknologi Malaysia, 2007